PENGATUR KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT SEKAWAN KONTRINDO PALEMBANG - Firdaus Sianipar; Arifin Zaini (Fakultas Ekonomi Universitas Tridinanti Palembang, 2015)
ABSTRACT This study aims to determine and identify how much influence the health and safety of employees can affect the productivity of work. The sample used in this study is saturated sample by using the entire population employed about 49 people were used as the respondents, with data collection questionnaires, by using variable research is Health, Safety, Productivity . Data validity was tested using Pearson product moment correlation, and fatherly test level using Cronbach Alpha reliability with, then the data is processed by multiple linear regression analysis. Hypothesis testing using F test and t test with significance level of 5%. Researchers using SPSS Version 16. tools for Windows. Multiple linear regression analysis showed that occupational health (X1) and Safety (X2) has an influence on employee work productivity (Y). from the calculation of the F test, it can be seen that the F test (25.507)> F table (3,19). So Ha which says there is a significant effect of occupational health and safety of employees working on productivity. Results of tests performed with partial regression analysis occupational health variables (X1) has t X1 3.017> 2.001 t table, then Ha Ho accepted and rejected, this means that there is significant influence by the occupational health variables (X1) of the Work Productivity of employees. (Y). Safety variables (X2) has t X2 3.364> 2.001 t table, then Ha Ho accepted and rejected, this means that there is a significant influence by the variable Safety (X2) of the Work Productivity employees of PT Sekawan Kontrindo Palembang (Y). This means health variables (X1) and Safety (X2) significantly influence labor productivity. See from these results that the health and safety it is necessary to increase employment in the company. Key Word: Health and Safety, Productivity, employees